How ICTs and Collaboration with NRENs are Changing the Face of Higher Education - Carabine, Deirdre (My University, 2016)
This paper presents a sustained argument for the university of today, and its academic and research staff, to make the best use of the facilities afforded by RENs to ensure that ICTs become the foundation for academic networking and collaboration. The paper examines the role of the REN and its changing goals, the challenges faced when using out-dated teaching methodologies in the classroom, and the role that RENs can play in networking or peering individuals, research communities, and institutions. I also make the case for a closer relationship between academic staff and their REN so that peering can become a seamless way to bring a nation’s teaching and research staff, and their institutions, together to bring universities fully into the technological world of the twenty-first century.
Keywords: ICT; Collaboration; NREN; Higher Education